How to overcome barriers to publication in low‐ and middle‐income countries: Recommendations from early career psychiatrists and researchers from around the world. (7th December 2021) - El Halabi, Sarah; Abbas, Zargham; Adesokun, Fisayo; Adiukwu, Frances; Ashrafi, Agaah; de Filippis, Renato; Handuleh, Jibril; Jaguga, Florence; Karaliuniene, Ruta; Kilic, Ozge; Nagendrappa, Sachin; Ojeahere, Margaret; et al.
Abstract: There is an increasing movement toward international collaboration and global discussion in mental health. If provided with the right opportunities, early career psychiatrists (ECPs) and researchers in mental health can contribute meaningfully to this discussion. However, they often experience multiple barriers when attempting to add their voices via academic publications. We represent a diverse group of ECPs and researchers from all six World Health Organization regions. In this piece, we discuss these barriers, grounded in our first‐hand experiences, and put forth a series of recommendations. The most potentially beneficial and immediate way forward is ensuring a much‐needed mentorship and support, particularly for low‐ and middle‐income countries. In this regard, international organizations, especially those with a particular focus on education, such as the Section on Education in Psychiatry of the World Psychiatric Association, can play a pivotal role.